2001
DOI: 10.1016/s0736-0266(00)90010-x
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal repair using engineered tissue

Abstract: In this study, devitalized meniscal tissue pre-seeded with viable cultured chondrocytes was used to repair a bucket-handle incision in meniscal tissue transplanted to nude mice. Lamb knee menisci were devitalized by cyclic freezing and thawing. Chips measuring four by two by one-half millimeters were cut from this devitalized tissue to serve as scaffolds. These chips were then cultured either with or without viable allogeneic lamb chondrocytes. From the inner third of the devitalized meniscal tissue, rectangle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 24 publications
2
64
0
4
Order By: Relevance
“…Previous studies of our group demonstrated the feasibility and the efficiency of bonding cartilaginous [25,26,28,32] and meniscal [27,29] tissue with cellular fibrin glue. According to this experience, we have designed the present study in order to evaluate the potential of chondrocytes-embedded fibrin glue for bonding meniscal slices in a nude mouse model.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies of our group demonstrated the feasibility and the efficiency of bonding cartilaginous [25,26,28,32] and meniscal [27,29] tissue with cellular fibrin glue. According to this experience, we have designed the present study in order to evaluate the potential of chondrocytes-embedded fibrin glue for bonding meniscal slices in a nude mouse model.…”
Section: Discussionmentioning
confidence: 88%
“…Menisci were harvested from pig knees and devitalized by freeze/thaw cycles using a standardized protocol [27]. Radial slices were obtained from the menisci by sectioning its circumferential fibers.…”
Section: Overview Of Methodsmentioning
confidence: 99%
“…Fibrochondrocytes have been used many times in the past (Aufderheide and Athanasiou, 2005;Hidaka et al, 2002;Ibarra et al, 1997;Isoda and Saito, 1998;Martinek et al, 2005;Mueller et al, 1999;Pangborn and Athanasiou, 2005b;Walsh et al, 1999) and can be used to create constructs with a predominantly collagen type I matrix, similar to the outer meniscus . For the inner meniscus, chondrocytes have recently received increased attention (Peretti et al, 2001(Peretti et al, , 2004Puelacher et al, 1994;Weinand et al, 2006). With the goal of increasing the collagen type II and proteoglycan components of the neotissue, the two cell types have been co-cultured to create an extracellular matrix composed of collagen I, collagen II, and proteoglycans, thus expanding the breadth of tissue characteristics that could be generated .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that tissue engineering has the potential to yield meniscus substitutes which could, immediately after implantation, protect articular cartilage by distributing and absorbing physiological loads [9][10][11][12]. The generation of meniscus grafts with a sufficient level of functionality could be facilitated by the application of defined regimes of physical conditioning in bioreactors, similarly to what has been introduced in cartilage tissue engineering [13,14].…”
Section: Introductionmentioning
confidence: 99%